Heterozygous mutation of Ush1g/Sans in mice causes early-onset progressive hearing loss, which is recovered by reconstituting the strain-specific mutation in Cdh23†. (2nd March 2016) - Miyasaka, Yuki; Shitara, Hiroshi; Suzuki, Sari; Yoshimoto, Sachi; Seki, Yuta; Ohshiba, Yasuhiro; Okumura, Kazuhiro; Taya, Choji; Tokano, Hisashi; Kitamura, Ken; Takada, Toyoyuki; Hibino, Hiroshi; et al.
Abstract : Most clinical reports have suggested that patients with congenital profound hearing loss have recessive mutations in deafness genes, whereas dominant alleles are associated with progressive hearing loss (PHL). Jackson shaker ( Ush1g js ) is a mouse model of recessive deafness that exhibits congenital profound deafness caused by the homozygous mutation of Ush1g / Sans on chromosome 11. We found that C57BL/6J- Ush1g js /+ heterozygous mice exhibited early-onset PHL (ePHL) accompanied by progressive degeneration of stereocilia in the cochlear outer hair cells. Interestingly, ePHL did not develop in mutant mice with the C3H/HeN background, thus suggesting that other genetic factors are required for ePHL development. Therefore, we performed classical genetic analyses and found that the occurrence of ePHL in Ush1g js /+ mice was associated with an interval in chromosome 10 that contains the cadherin 23 gene ( Cdh23 ), which is also responsible for human deafness. To confirm this mutation effect, we generated C57BL/6J- Ush1g js /+, Cdh23 c.753A / G double-heterozygous mice by using the CRISPR/Cas9-mediated Cdh23 c.753A > G knock-in method. The Cdh23 c.753A / G mice harbored a one-base substitution (A for G), and the homozygous A allele caused moderate hearing loss with aging. Analyses revealed the complete recovery of ePHL and stereocilia degeneration in C57BL/6J- Ush1g js /+ mice. These results clearly show that the development of ePHL requires at least two mutant alleles of the Ush1g and Cdh23 genes. Our results also suggest that because the SANS and CDH23 proteins form a complex in the stereocilia, the interaction between these proteins may play key roles in the maintenance of stereocilia and the prevention of ePHL.